Characterisations and DSSC efficiency test of TiO2nano-films formed by filtered cathodic vacuum arc deposition - C. Aramwit (2018)
Copyright © 2017 Inderscience Enterprises Ltd. For photovoltaic applications in dye-sensitised solar cells (DSSC), used as a wide band semiconductor layer, titanium dioxide (TiO 2 ) nano-films were formed by the filtered cathodic vacuum arc deposition (FCVAD) technique using Ti as the cathode and controlled oxygen (O 2 ) gas inlet under varied deposition and post-deposition annealing conditions. The deposition conditions included the O 2 pressure as the key parameter and others such as deposition time and bias. The work was aimed at investigating the FCVAD condition effect on the TiO 2 film characteristics and thus the solar cell efficiency. The formed films were characterised using optical microscopy, scanning electron microscopy (SEM), atomic force microscopy (AFM), energy-dispersive X-ray spectroscopy (EDS), Raman spectroscopy and scanning photoemission microscopy (SPEM) techniques. All the characterisations revealed that the film transparency increased and thickness decreased to a nanoscale with increasing of the O 2 pressure, the transparent deposited films contained stoichiometric titanium and oxygen under the medium O 2 pressure, the as-deposited films were TiO 2 containing some rutile but without anatase, and the annealing improved the film quality by introducing anatase and increasing the Ti-oxide. Test of the films for the DSSC-photovoltaic property efficiency showed that the efficiency of using the annealed films was 10 4 times that of using the as-deposited films, indicating the crucial significance of the anatase.